Histological Effects of Letrozole and Clomiphene Citrate on Albino Rat Ovary after Consecutive 1-4 Estrous Cycles - Fauzia Qureshi , Shahnila Nadir , Nida Qasim Hayat , Maryam Ashraf , Fauzia Qureshi , Shahnila Nadir , Nida Qasim Hayat , Maryam Ashraf (Journal of Rawalpindi Medical College, 2017)
Background:To observe the histological effects of letrozole and Clomiphene citrate on albino rat ovary after consecutive 1-4 estrous cycles. Methods: An experimental study was carried out on eighty four adult female Albino rats. The rats were equally divided into three groups. Vaginal smear cytology was performed to determine the phases of estrous cycle. The group A was given normal saline orally and served as control. Group B was given letrozole(Femara) at dose 5mg/kg orally and group C was given clomiphene citrate at dose 100ug/kg orally. Each group was further subdivided into four subgroups on the basis of duration of treatment. Ovarian sections were made and stained with Haematoxylin and Eosin. Number of antral follicle in both ovaries of each subgroups were counted and were analyzed using SPSS 20.0. Mean ± S.D. Results: Morphometric and statistical analysis revealed that number of antral follicle was significantly increased with both letrozole and clomiphene citrate as compared to control. However marked increase in number of antral follicle and development of cystic follicles was observed in clomiphene citrate group. Conclusion: Letrozole and clomiphene citrate both have improved folliculogenesis. However letrozole is more effective and safe for ovulation induction